La téléconsultation : un levier pour rehausser l’accès aux services de santé en français pour les communautés francophones en situation minoritaire de l’Ontario - Dorion, Michelle; Giroux, Isabelle; Dionne, Éric (Reflets, 2026)
Les écrits démontrent que l’accessibilité aux services de santé en français est lacunaire chez les communautés francophones vivant en situation minoritaire (CFSM). Cette barrière linguistique est alarmante, car elle peut avoir des conséquences graves sur la qualité des soins et sur la sécurité des patientes et patients francophones. Face à cette réalité, la téléconsultation représente une solution technologique prometteuse permettant d’élargir l’offre des services de santé en français pour les CFSM. Ainsi, cet article présente un point de vue critique quant à l’utilisation de la téléconsultation en abordant les avantages et les limites qui lui sont associés. Les possibilités qu’offre ce dispositif pour rehausser les services de santé en français chez les CFSM seront également abordées en tenant compte des données recueillies auprès de patientes et patients ainsi que des prestataires de soins de santé francophones concernant leurs expériences avec l’utilisation de la téléconsultation à l’Hôpital Montfort, un centre hospitalier francophone en Ontario. Research shows that access to healthcare services in French is deficient in Francophone minority communities. This language barrier is alarming as it can have negative impacts on the quality and safety of care provided for Francophone patients. Faced with this reality, teleconsultation is a promising technological solution to enhance the offer of services in French for Francophone minority communities. Thus, this article presents a critical view on the use of teleconsultation by addressing its associated benefits and limitations. The possibilities this technology offers to enhance health services in French to Francophones living in a linguistic minority community will also be addressed by taking into account the experience with teleconsultation of French-speaking patients and healthcare providers at Montfort Hospital, a Francophone community hospital in Ontario.

L’usage de technologies de santé pour accéder à des soins virtuels : une enquête exploratoire pour mieux comprendre les besoins et attentes des francophones de l’Ontario - Grosjean, Sylvie; Giguère, Lauriane; Lessard, Lysanne; Dionne, Émilie (Minorités linguistiques et société, 2024)
Dans cet article, nous présentons les résultats d’une étude visant à répondre à la question suivante : quels usages des technologies numériques de santé sont jugés accessibles et acceptables par les francophones de l’Ontario? Les résultats de cette enquête exploratoire montrent que l’accessibilité et l’acceptabilité des technologies de santé pour soutenir l’offre de soins virtuels chez les francophones de l’Ontario dépendent de plusieurs facteurs liés : a) à leur utilité perçue, b) à leur valeur sociale et leur intégration dans des usages existants, et c) à l’offre des technologies accessibles en français – de leur conception au support offert pour en accompagner les usages. Les résultats de l’étude nous invitent à considérer les questions à la fois communicationnelles (concordance linguistique patient/technologie), organisationnelles (intégration dans des pratiques et structures existantes) et éthiques qu’implique l’usage des technologies de santé visant à soutenir l’offre de soins virtuels pour les francophones de l’Ontario. Mots-clés : soins virtuels, technologies numériques de santé, acceptabilité, francophones, Ontario

Le programme de télésanté de prévention des chutes Marche vers le Futur : développement et retombées d’une communauté de pratique franco-canadienne - O’Neil, Jennifer; Dionne, Nathalie; Cardinal, Dominique; Savard, Jacinthe (Minorités linguistiques et société / Linguistic Minorities and Society, 2025)
Résumé Le programme de télésanté Marche Vers le Futur (MVF) a eu un impact positif sur le bien-être des personnes âgées francophones et sur leur accès aux services de prévention des chutes au Canada. L’objectif de ce projet était de développer et de mettre en place une communauté de pratique (CdP) facilitant le partenariat et le partage des connaissances entre les animateurs du programme MVF. La création de cette CdP a permis à vingt-deux animateurs de cinq provinces de partager des stratégies de recrutement, de promotion du programme et de sensibilisation quant aux besoins des personnes âgées francophones au pays. Quatre rencontres virtuelles ont permis d’identifier les obstacles à la pérennité de MFV, les facteurs facilitant la mobilisation des connaissances ainsi que les initiatives de formation continue. La CdP a permis de renforcer les réseaux de partenariat entre les chercheurs et les animateurs du programme MVF, ce qui pourrait avoir un impact important sur l’équité en santé chez les personnes âgées francophones vivant en situation minoritaire au Canada. Abstract Marche vers le Futur (MVF) is a telehealth program that has demonstrated a positive impact on the access to fall prevention services in Canada and the wellness of older Francophone adults living in minority situations. This project aimed to develop and implement a community of practice (CoP) to facilitate partnership and knowledge-sharing between MVF program facilitators across francophone communities in Canada. The creation of this CoP enabled twenty-two facilitators from five provinces to share strategies for recruiting, promoting, and sustaining the program as well as continuing to raise awareness around the importance of health prevention services tailored for older Francophone adults in Canada. Four virtual meetings were held to identify sustainability barriers, knowledge mobilisation facilitators, and continuing education initiatives. The CoP allowed to strengthen the partnership between researchers and program facilitators across diverse provinces which could impact health equity among older Francophone adults living in minority communities in Canada.

Reach, adoption, and implementation strategies of a telehealth falls prevention program: perspectives from francophone communities across Canada. - O’Neil, Jennifer; Dionne, Nathalie; Marchand, Sylvie; Cardinal, Dominique; Handrigan, Grant; Savard, Jacinthe (Health Promotion and Practice, 2024)
Introduction. A fall may impact a person’s physical, emotional, and psychological well-being. Fall prevention programs are being implemented to reduce these negative outcomes. However, linguistic barriers in health services may reduce access to such prevention programs. A telehealth fall prevention program was designed to increase access to such programs in French for Francophone minority communities in Canada. This capacity-building project aimed to support community partners to deliver this telehealth program and document strategies used to reach, adopt, and implement the program within various Francophone and Acadian Minority Communities. Methods. A sequential explanatory mixed methodology was used to document reach, adoption, and implementation strategies and describe the lived experiences of program facilitators and organization representatives. Reach, adoption, and implementation were documented and analyzed descriptively, while lived experiences were analyzed using content analysis following the Consortium Framework for Implementation Research. Results. Twelve organization representatives or program facilitators from eight organizations operating in four different provinces participated in the study. Three themes emerged from the qualitative data on reach and adoption: external context, internal context, and capacity building. Four themes were identified as barriers and facilitators to implementation: level of preparation and time management, interpersonal relations and telepresence, exercise facilitation and safety, and technological problem-solving. Conclusion. Using tailored reach and adoption strategies such as prioritizing provinces with higher proportions of needs and training local community program facilitators may lead to the successful implementation of a new telehealth fall prevention program. Results from this study could potentially inform other primary prevention programs or telehealth program implementation.